Schisantherin A inhibits cell proliferation by regulating glucose metabolism pathway in hepatocellular carcinoma - Feng, Fan; Pan, Lianhong; Wu, Jiaqin; Liu, Mingying; He, Long; Yang, Li; Zhou, Wei (Frontiers in Pharmacology, 2022)
Schisandrin A (STA) is a traditional Chinese medicine extracted from the plant Schisandra chinensis, which has a wide range of anti-inflammatory, antioxidant and other pharmacological effects. The aim of this study was to investigate the anti-hepatocellular carcinoma effect of STA and its possible mechanism. The results showed that STA significantly inhibited the proliferation and migration of Hep3B and HCCLM3 cells in vitro in a concentration dependent manner. Transcriptome sequencing results showed that STA could significantly inhibit gene transcription, and KEGG pathway analysis was significantly enriched in Galactose metabolism and Fructose and pentose phosphate metabolism. Further metabolomics analysis confirmed this result, indicating that STA significantly inhibited the glucose metabolic pathway in cells. In vivo experiments showed that STA had a significant inhibitory effect on tumor growth. The results show that STA can inhibit cell proliferation by regulating glucose metabolism, thus showing anti-tumor effect, and may become a candidate drug for the treatment of liver cancer.